Caffeine Adsorptive Performance and Compatibility Characteristics (Eisenia Foetida Savigny) of Agro-Industrial Residues Potentially Suitable for Vermifilter Beds - Villamar-Ayala, C (Elsevier B.V., 2021)
The caffeine adsorptive performance and compatibility characteristics (Eisenia foetida Savigny) of rice husk, peanut shell, corn cob and coconut fiber were studied, aiming to assess the suitability of these residues for vermifilter beds. For this purpose, the agro-industrial residues were characterized and the E. foetida Savigny compatibility was determined by acute and chronic toxicity tests. Batch adsorption tests were performed using caffeine solutions. Optimal adsorption conditions, kinetic models, isotherm type and the influence of three particle sizes (120–150, 300–600, 800–2000 μm) in the caffeine removal were determined. Coconut fiber (120–150 μm) proved to be the most efficient residue for the caffeine removal (94.2%), requiring 4 g/L for 30 min. However, coconut fiber was the less compatible for earthworms (14d-LC50 = 82%). The results obtained allow to define adequate strategies, such as mixing highly adsorptive residues with the more compatible ones, to choose the most effective materials for vermifiltration technologies. © 2021